TaME-seq2 v2 - jean-marc not provided; Milan Stosic; Alexander Hesselberg; trinro not provided (2023)
Tagmentation-assisted multiplex PCR enrichment sequencing for viral genomic profiling (TaME-seq2). Viral genome and integration enrichment library preparation protocol. Manuscript: TaME-seq2: Tagmentation-assisted multiplex PCR enrichment sequencing for viral genomic profiling. Alexander Hesselberg Løvestad, Milan S. Stosic, Jean-Marc Costanzi, Irene Kraus Christiansen, Hege Vangstein Aamot, Ole Herman Ambur, Trine B. Rounge medRxiv 2022.12.22.22283851 doi: https://doi.org/10.1186/s12985-023-02002-5 Before starting: Prepare samples consisting of extracted DNA or reverse transcribed cDNA. The method consists of three main parts: Part 1: Tagmentation of samples using the Illumina DNA Prep kit. Part 2: Multiplex PCR reaction of tagmented DNA/cDNA, using virus-specific primers and i5/i7 indexes. Part 3: Clean-up and size selection using purification beads/Ampure XP beads.